PENGARUH MOTIVASI INTRINSIK DAN KOMITMEN PROFESI TERHADAP PERENCANAAN KARIR DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI DI KANTOR BALAI WILAYAH SUNGAI SUMATERA II - Suparwasesa . (Universitas Islam Islam Sumatera Utara, 2019)
The problem formulation in this study is how intrinsic motivation affects the employee's career planning. How to influence professional commitment to employee career planning. How to influence intrinsic motivation towards employee performance. How to influence the profession commitment to employee performance. How to influence the profession commitment to employee performance. The purpose of this research is to know and analyze the influence of intrinsic motivation towards employee career planning. To know and analyze the influence of professional commitment to employee career planning. To know and analyze the influence of intrinsic motivation to employee performance. To know and analyze the influence of professional commitment to employee performance. To know and analyze the influence of professional commitment to employee performance. The samples in this study amounted to 82 employees. The data analysis techniques in this study used descriptive analysis and track analysis (path analysis).The results of this study explained that the direct influence of the intrinsic motivation variable towards employee career planning is 0.123. The direct influence of the profession commitment to career planning officers amounted to 0.338. Direct influence of intrinsic motivation variable to employee performance of 0.273. Direct influence of professional commitment variable to 0.518 employee performance. Direct influence of career planning variables to employee performance of 0.273. The indirect influence of the motivation variable is intrinsic to performance through employee career planning of 0.074. Effect of indirect variables of the profession commitment to performance through employee career planning of 0.141. The total effect of an intrinsic motivation for variable performance through employee career planning is 0.347. The total effect of a professional variable commitment to performance through employee career planning is 0.791.